Analisis Wacana Pesan Dakwah Islam di Pro 1 Lembaga Penyiaran Publik (LPP) RRI Padang - Anrial Anrial (Jurnal Dakwah dan Komunikasi, 2016)
The development of information technology media is growing day by day, as well as a variety of informations given to the public which are very diverse and purposed to provideinsight, entertainment, and knowledge for the community, so that the quality of any informations conveyed must be kept. Similar to the LPP RRI Padang, which also do not want to miss in broadcasting which he has. The religious proselytizing program in LPP RRI becomes a main menufor RRI Padang every day. Its objective is to provide religious knowledge for surroundings by the determined methods appropriate to the program. However, to improve the quality, anin-depth analysis for the message delivered is needed, so that the future proselytizing material delivered will have a goodgrade and quality. The method used in analyzing these messages is a discourse analysis using Van Dijk framework, so that eachdelivered message can be analyzed in the form of thematic, schematic, semantic, syntactic, stylistic, and rhetorical. By using the framework, there will be some assessments of the messages, and may be some improper things which is meant the language used in preaching is rather ambiguous or there is no emphasizingvalues (semantic to rhetorical) to the message sent by preachers in media such as radio